Reign of the quisling-rodents - Ngolle-Metuge (Langaa Research & Pub., 2010)
How else does the ramified phenomenon of greed (corruption, nepotism, extreme self-aggrandizement, megalomaniac tendencies etc) become nefarious to both the physical and mental worlds of a people either individually or collectively? It brings about a retrogressing, catabatic state in their evolution in both regards, eating back into the socio-economic and political set up of a given society as well as unquestionably impairing the mindset of its people. Reign of the Quisling-Rodents tells of the gradual bane of a society to perdition which is not so much due to its dehumanizing physical quality as it is to a collective consciousness which is rooted in apocalyptic rapacity. It delves into the tenebrous mindset of a generation, moving from the metal holocaust that greed engenders to its actual physical manifestation as seen in the various situational anathemas which many of the poems lament. The bottom line of all that the mind and the physical being suffer is an irreparably worsted governance. --Book Jacket.